MEDIASI KETERLIBATAN KARYAWAN TERHADAP HUBUNGAN MANAJEMEN BAKAT DENGAN KINERJA PEGAWAI - Atika Anggi Hafsara; Mukhsin, Moh. (Lembaga Penelitian, Publikasi dan Pengabdian pada Masyarakat (LP3M) Nobel Indonesia, 2024)
This research aims to investigate and analyze the influence of management talent on employee performance, by considering the role of employee involvement as a mediator. The methodological approach used is quantitative descriptive, with Bank BTN Syariah Serang as the research object and involving 100 respondents as the research sample. Survey data was obtained using a 1-1 interval scale and then analyzed using Smart PLS version 4.0 software. The findings of this research imply that: 1) talent management does not have a positive impact on employee performance; 2) talent management has a positive and significant impact on employee engagement; 3) employee involvement has a positive and significant impact on employee performance; 4) talent management has a positive impact on employee performance through the mediation of employee involvement